Factors Associated with Hypertension-Risk Eating Behavior in the Elderly in the Work Area of ​​the Mining Health Center: Faktor – Faktor Yang Berhubungan Dengan Perilaku Makan Beresiko Hipertensi Pada Lansia Di Wilayah Kerja Puskesmas Tambang - Popi Purnama Sari; Emy Leonita; Jasrida Yunita; Siska Mayang Sari; Raviola Raviola (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Hypertension is a major risk factor that leads to cardiovascular disease. Hypertension can be controlled by regulating eating behavior, where the percentage of behavior less consumption of fruits and vegetables is the highest percentage, namely 95.4%. The purpose of this study was to determine the factors associated with eating behavior at risk of hypertension in the elderly in the working area of ​​the Tambang Health Center, Tambang District in 2022. This research method was quantitative with a cross sectional design. The sample of this research is 126 people taken by consecutive sampling technique. The analysis used is univariate and bivariate with chi-square test. The results showed that there was a relationship between age (p = 0.045, OR=2,439 ), gender (p = 0.0026, OR = 2.627 ), attitude (p = 0.019, OR = 2.796 ), knowledge (p = 0.015, OR = 2.851 ) , the role of health workers (p = 0.007, OR = 3.544 ), family support (p = 0.001, OR = 3.544 ) and the unrelated, namely education (p = 0.507) and distance to health facilities (p = 0.379), it can be concluded that factors related to eating behavior at risk of hypertension in the elderly in the work area of ​​the Tambang Health Center, Tambang District in 2022 include, age, gender, attitude, knowledge, role of health workers and family support Suggestions for the elderly are expected to routinely check blood pressure at the nearest posbindu and for health workers to increase the role of health promotion and increase the knowledge of the elderly, especially knowledge about the recommended consumption of hypertension drugs.